2018
DOI: 10.1177/0031721718762419
|View full text |Cite
|
Sign up to set email alerts
|

Why we need a new approach to teaching digital literacy

Abstract: In recent years — and especially since the 2016 presidential election — numerous media organizations, newspapers, and policy advocates have made efforts to help Americans become more careful consumers of the information they see online. In K-12 and higher education, the main approach has been to provide students with checklists they can use to assess the credibility of individual websites. However, the checklist approach is outdated. It would be far better to teach young people to follow the lead of profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 3 publications
0
56
0
11
Order By: Relevance
“…Information literacy instruction in schools has not kept pace with the internet's evolution. In U.S. schools, many K–12 students are encouraged to search only in library databases or on .edu websites for their research papers; otherwise, they are told to evaluate websites based on domain name and features such as currency and relevance, often arranged in a checklist or as an acronym (Breakstone et al., ; Metzger, ). These checklists assume that credibility judgments can and should be made by closely examining a single webpage alone, and the Web 2.0 perspectives of these heuristics are often misleading in the current Web 3.0 environment (Breakstone et al., ; Kohnen, in press).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Information literacy instruction in schools has not kept pace with the internet's evolution. In U.S. schools, many K–12 students are encouraged to search only in library databases or on .edu websites for their research papers; otherwise, they are told to evaluate websites based on domain name and features such as currency and relevance, often arranged in a checklist or as an acronym (Breakstone et al., ; Metzger, ). These checklists assume that credibility judgments can and should be made by closely examining a single webpage alone, and the Web 2.0 perspectives of these heuristics are often misleading in the current Web 3.0 environment (Breakstone et al., ; Kohnen, in press).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In U.S. schools, many K–12 students are encouraged to search only in library databases or on .edu websites for their research papers; otherwise, they are told to evaluate websites based on domain name and features such as currency and relevance, often arranged in a checklist or as an acronym (Breakstone et al., ; Metzger, ). These checklists assume that credibility judgments can and should be made by closely examining a single webpage alone, and the Web 2.0 perspectives of these heuristics are often misleading in the current Web 3.0 environment (Breakstone et al., ; Kohnen, in press). A decade's worth of research studies have found that in the absence of adequate instruction, students struggle to make credibility judgments (e.g., Brand‐Gruwel, Wopereis, & Walraven, ; Eynon & Geniets, ; Thomm & Bromme, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Critics of the checklist have underscored major weaknesses of the method, such as how it oversimplifies a nuanced process (Meola, 2004) or does not reflect the many different types of information-sharing sites that now exist (Ostenson, 2014). These arguments hold more weight in the current fake news-saturated landscape, especially those suggesting checklist tools can produce false positives when used on certain questionable sources (Breakstone, McGrew, Smith, Ortega, & Wineburg, 2018;Caulfield, 2016). This move away from checklist evaluation tools, in conjunction with the recent emphasis on fake news in library instruction, suggests new approaches are needed to teach students to detect misinformation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There has also been a shift in expectations of availability and quality among consumers of this information, particularly among students (Heick, 2018;Horrigan and Rainie, 2002). Students have difficulty evaluating which information sources are credible (Breakstone et al, 2018;McGrew et al, 2018;Wineburg et al, 2016). When confronted by information challenges, students often turn to friends for assistance before turning to their professor, librarian, or other formal source of support (Beisler and Medaille, 2016).…”
Section: Introductionmentioning
confidence: 99%